Morphological and Molecular Characterization of Heterodera schachtii and the Newly Recorded Cyst Nematode, H. trifolii Associated with Chinese Cabbage in Korea - Mwamula, Abraham Okki (Plant Pathol J, 2018)
The sugar beet cyst nematode, Heterodera schachtii is a well known pathogen on Chinese cabbage in the highland fields of Korea. However, a race of cyst forming nematode with close morphological resemblance to H. trifolii was recently isolated from the same Chinese cabbage fields. Morphological species differentiation between the two cyst nematodes is challenging, with only minor differences between them. Thus, this study described the newly intercepted H. trifolii population, and reviewed morphological and molecular characteristics conceivably essential in differentiating the two nematode species. A comparison of morphometric measurements of both infective juveniles and vulval cones of cysts showed significant differences between the two cyst nematodes. When total RNA and genomic DNA were extracted from a mixed field population, COI genes and ITS regions were clearly amplified with primers of the two Heterodera species, suggesting that Heterodera population collected from the Chinese cabbage field consisted of a mixture of two species. COI and ITS of H. trifolii were predominantly amplified from nucleotides prepared from H. trifolii monoxenic population whereas those of H. schachtii were strongly detected in H. schachtii monoxenic cultures. Thus, this study confirms the coexistence of the two species in some Chinese cabbage fields; and the presence of H. trifolii in Korea is reported here for the first time.